The Management of Metastatic Bone Disease with the Combination of Bisphosphonates and Radiotherapy: From Theory to Clinical Practice - Vassiliou, V.; Kardamakis, D. (Anti-Cancer Agents in Medicinal Chemistry, 2009)
Bone metastases are common in the event of malignancy and are inevitably associated with serious complications that may deteriorate the quality of life (QOL) of patients and threaten life. Both radiotherapy (RT) and bisphosphonates (BPs) have an established role in the management of metastatic bone disease. Many clinical trials have demonstrated their effectiveness when used as sole treatment modalities, but only a few have evaluated their therapeutic value when applied concomitantly. We herein discuss the pathophysiology of bone metastases and the potential interactions between RT and BPs. Moreover, the results of both animal models and clinical studies are presented in detail. Apart from aspects of normal tissue tolerance, other interactions include spatial cooperation and additive or super-additive effects. The latter brings about a synergistic activity that results in an enhanced reossification, improved bone stability and microarchitecture, and increased mechanical strength, as documented through animal model studies. The results of published clinical studies investigating the effectiveness of concomitant application of RT and BPs are promising, reporting a significant clinical and radiologic response. More specifically, a significant reduction of pain scores and a worth noticing improvement in QOL and performance status (PS) were noted, accompanied by a considerable increase in bone density. Pain relief was accompanied by a marked reduction in analgesic opioid need. The enhanced reossification may be responsible for the improved therapeutic response, since it was shown that the correlation between pain and bone density is negative and strong. Although promising and encouraging, the results of such studies should be corroborated by larger, randomized trials.
Keywords: zoledronic acid